The mechanism of the terahertz spectroscopy for oil shale detection. (15th October 2018) - Zhan, Honglei; Chen, Mengxi; Zhao, Kun; Li, Yizhang; Miao, Xinyang; Ye, Haimu; Ma, Yue; Hao, Shijie; Li, Hongfang; Yue, Wenzheng
Abstract: Terahertz time domain spectroscopy (THz-TDS) can directly detect oil shales. The absorption coefficient is related to the oil content in the rock. This value can be compared across regions to measuring the oil content in the oil shale. Here we studied three regions and included scanning electron microscope (SEM) and thermogravimetric analysis (TGA) to verify the amount of kerogen within oil shale prior to the constitution of the mineral matrix via the THz response. Aromatic and the aliphatic compounds contribute to the absorption of shales in the THz range due to the relatively high intramolecular interactions—this reveals the mechanism of THz radiation penetration through shales as reported in previous reports. The differences in quantum structure of a molecule between organic and inorganic materials suggest that THz-TDS can be applied to geophysical prospecting and improve the effectiveness of the detection of organics in oil shale. Highlights: Terahertz spectroscopy was used to directly detect oil shales. Terahertz absorption index depends on the kerogen content in oil shales. Aromatic and aliphatic compounds contribute to the absorption of oil shales.